The conundrum of COVID-19 and the sports industry: when saving lives is more important than entertainment - Nxumalo, S. A. (From High-risk Sports to Sports as High Risk: Crisis, Captulation and Creativity during COVID-19, 2020)
The advent of COVID-19 has thrown the world of sports into disarray. Far and wide, numerous sports codes, leagues, and federations suspended their activities. They had their operational models adapted as a safety precaution to ensure that minimal human life is lost. Social distancing, one of the critical measures in combating COVID-19, is not always practical for both spectators and participants in sports events. In this chapter, I interrogate the impact of COVID-19 on the sports industry. I argue that COVID-19 has exposed the long-standing neoliberal operational model that has been followed by the world of sports as being flawed and in need of a massive change. I argue that, perhaps, COVID-19 was the necessary chaos that the sports industry needed to usher in a `new paradigm.` The sports industry ought to keep up with new trends, adapt and embrace new strategies and technologies to continue to offer sporting activities when `live` game participation and attendance are not an option amid large scale pandemics such as COVID-19. I recommend that the lessons learned from challenges imposed by COVID-19 should transform sports into new frontiers never imagined before, in which saving lives are more important than entertainment.